Prediction Errors and Accuracy of Intraocular Lens (IOL) Calculation Formulas in Pediatric Eyes - Fitri Muslim; Julie Dewi Barliana (Majalah Oftalmologi Indonesia, 2020)
Background: Acquiring an accurate intraocular (IOL) power in children undergoing cataract surgery is challenging. Different IOL calculation formulas in children have been previously studied to achieve a precise prediction of the IOL power. Larger errors in IOL formula predictions have shown in several studies on children as future growth of the eye affects the keratometry readings and axial length. Prediction error (PE) and absolute prediction error (APE) can be effective indicators in assessing the accuracy of IOL power calculation formulas. Therefore, this review aims to investigate the accuracy of IOL power calculation formulas in pediatric eyes by measuring PE and/or APE value. Methods: A comprehensive search was conducted from various electronic databases (Pubmed, Clinical Key, and Ophthalmology Advance) using relevant search terms. Included studies were screened using predefined inclusion and exclusion criteria to identify comparative studies comparing the accuracy of IOL calculation formulas in pediatric patients. Result: Ten studies including 964 eyes were identified to compare different IOL formulas: Hoffer Q, SRK/T, SRK II, Holladay 1, and Holladay 2. Smaller prediction error is related to better postoperative refraction. Among included studies, Holladay 2 had the smallest mean prediction errors (PE), while SRK/T formula was the best formula of all included studies in pediatric patients as it had the smallest mean absolute prediction errors (APE). Hoffer Q also had the smallest mean APEs in shorter eyes (axial length <22 mm). Conclusion: This study demonstrates that none of the established formulas found to be more superior than any other formulas in predicting IOL power in children. Biometry examination in patients with less than one year of age tends to show a lower accuracy.